Pengaruh Live Streaming Tiktok sebagai Media Promosi terhadap Minat Beli Konsumen Mahasiswa Vokasi - Dinanty Klahirana Pangestu (Asosiasi Ahli Administrasi Indonesia, 2023)
The aim of this research is to determine the influence of TikTok live streaming on consumer buying interest, especially among vocational students in Indonesia. A total of 101 respondents who were professional students and actively consumed streaming marketing content on the social media platform TikTok were taken as research samples. The analytical method used is descriptive, where data analysis is carried out using correlation and regression. Data collection was carried out by distributing questionnaires distributed on various social media platforms to respondents who met certain criteria. The research results show that marketing via TikTok as an advertising medium has a significant influence on purchasing interest of 53%, while the remaining 47% is influenced by several other factors which are not currently included in the variables studied.